The influence of adhesive material properties on the impact strength of adhesive block connections - Komorek, Andrzej; Godzimirski, Jan; Imiłowski, Szymon (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2023)
Adhesive connections are becoming increasingly popular in the construction of aircraft and other means of transport. Today, bonding is mainly used in the construction of helicopter fuselages, wings or lifting rotors. The increased popularity of bonding is forcing designers to seek new and improve research methods as well as enhancing the existing test methods which specify the static, fatigue or impact strength of joints. A variety of tests are used to determine the strength of structures, although new ones are constantly being sought so as to be applied more quickly and without specialised equipment. Current testing standards are also being modified in order to speed up and simplify the testing process, resulting in safer structures that use adhesive bonds. The aim of the research presented in this paper was to test whether there is a relationship between the mechanical properties of adhesive materials and the impact strength of adhesive block joints with a cylindrical top element. Steels S235, Raex 400 and PA6 aluminium alloy were used for the manufacture of the samples. From each material, 10 samples were prepared with upper elements of different diameters, namely: 17.8 mm, 12.6 mm and 8.9 mm. A pendulum hammer was used to determine the strength of the adhesive bond against dynamic load application. For the sake of the research, the authors used a modified PN-EN ISO 9653 with a mounted hammer equal to the maximum energy of 15 J. Lower failure energy was characteristic of samples made from material with a lower value of Young’s modulus (dural) and from steel with a lower yield strength. The connection failure energy grew with increasing the joint area, which was approximately parabolic.